Association of placental histopathological findings with COVID-19 and its predictive factors - Zeena Helmi; Hadeel Al-badri (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective: The aims of the study are to describe the association of coronavirus disease (COVID-19) with the abnormal histopathological findings in human placenta and to highlight the potential predictors of these histopathological findings. Methods: A retrospective cohort study, held in two obstetric units from January 2021- 2022, 34 patients who were confirmed cases of COVID- 19 were followed up till the time of delivery as their placenta were sent for histopathology. Patients diagnosed with other viral infections, chorioamnionitis, or were known case of as pre-term or term pre labour rupture of membrans (PROM) were excluded as well as pre exisiting diabetes mellitus or pre-eclampsia. Data analysis were performed using STATA software version 16. Result: Specific histopatological findings (fetal vascular malperfusion, maternal vascular malperfusion, inflammatory pathology and thrombotic finding) were significantly high among 13 (38.2%) of the study group who got infected earlier in pregnancy (P<0.001). The period between the diagnosis of COVID-19 and the delivery significantly increases the odds of the presence of pathological findings by 2.75 times for each week the patients getting infected earlier. Conclusion: Association of abnormal placental histopathological findings with COVID-19 infection in pregnancy and the potential predictor for the occurrence of placental findings is the longer duration between the diagnosis of the infection and the delivery.